Many new variable stars discovered in the core of the globular cluster NGC 6715 (M54) with EMCCD observations - Figuera Jaimes, Roberto; Schmidt, Robert W. (Arxiv, 2016)
We show the benefits of using Electron-Multiplying CCDs and the shift-and-add technique as a tool to minimise the effects of the atmospheric turbulence such as blending between stars in crowded fields and to avoid saturated stars in the fields observed. We intend to complete, or improve, the census of the variable star population in globular cluster NGC~6715. Our aim is to obtain high-precision time-series photometry of the very crowded central region of this stellar system via the collection of better angular resolution images than has been previously achieved with conventional CCDs on ground-based telescopes. Observations were carried out using the Danish 1.54-m Telescope at the ESO La Silla observatory in Chile. The telescope is equipped with an Electron-Multiplying CCD that allowed to obtain short-exposure-time images (ten images per second) that were stacked using the shift-and-add technique to produce the normal-exposure-time images (minutes). The high precision photometry was performed via difference image analysis employing the DanDIA pipeline. We attempted automatic detection of variable stars in the field. We statistically analysed the light curves of 1405 stars in the crowded central region of NGC~6715 to automatically identify the variable stars present in this cluster. We found light curves for 17 previously known variable stars near the edges of our reference image (16 RR Lyrae and 1 semi-regular) and we discovered 67 new variables (30 RR Lyrae, 21 long-period irregular, 3 semi-regular, 1 W Virginis, 1 eclipsing binary, and 11 unclassified). Photometric measurements for these stars are available in electronic form through the Strasbourg Astronomical Data Centre.
Gesehen am 06.11.2017